Venue-Based HIV Testing at Sex Work Hotspots to Reach Adolescent Girls and Young Women Living With HIV: A Cross-sectional Study in Mombasa, Kenya. (15th August 2020) - Ma, Huiting; Wang, Linwei; Gichangi, Peter; Mochache, Vernon; Manguro, Griffins; Musyoki, Helgar K.; Bhattacharjee, Parinita; Cholette, François; Sandstrom, Paul; Becker, Marissa L.; Mishra, Sharmistha
Abstract : Background: We estimated the potential number of newly diagnosed HIV infections among adolescent girls and young women (AGYW) using a venue-based approach to HIV testing at sex work hotspots. Methods: We used hotspot enumeration and cross-sectional biobehavioral survey data from the 2015 Transition Study of AGYW aged 14–24 years who frequented hotspots in Mombasa, Kenya. We described the HIV cascade among young females who sell sex (YFSS) (N = 408) versus those young females who do not sell sex (YFNS) (N = 891) and triangulated the potential (100% test acceptance and accuracy) and feasible (accounting for test acceptance and sensitivity) number of AGYW that could be newly diagnosed through hotspot-based HIV rapid testing in Mombasa. We identified the profile of AGYW with an HIV in the past year using generalized linear mixed regression models. Results: N = 37/365 (10.1%) YFSS and N = 30/828 (3.6%) YFNS were living with HIV, of whom 27.0% (N = 10/37) and 30.0% (N = 9/30) were diagnosed and aware ( P = 0.79). Rapid test acceptance was 89.3%, and sensitivity was 80.4%. There were an estimated 15, 635 (range: 12, 172–19, 097) AGYW at hotspots. The potential and feasible number of new diagnosis was 627 (310–1081), and 450 (223–776), respectively. Thus, hotspot-based testing could feasibly reduce the undiagnosed fraction from 71.6% to 20.2%. The profile of AGYW who recently tested was similar among YFSS and YFNS. YFSS were 2-fold more likely to report a recent HIV test after adjusting for other determinants [odds ratio (95% confidence interval): 2.2 (1.5 to 3.1)]. Conclusion: Reaching AGYW through hotspot-based HIV testing could fill gaps left by traditional, clinic-based HIV testing services. Abstract : Supplemental Digital Content is Available in the Text.